2015
DOI: 10.1007/s11832-015-0697-1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric orthopaedic lower extremity trauma and venous thromboembolism

Abstract: PurposeResearch on venous thromboembolism events (VTE), such as deep venous thrombosis (DVT) and pulmonary embolism (PE), in pediatric orthopaedic trauma patients is sparse. We describe the incidence in the USA of VTE associated with pediatric lower extremity orthopaedic trauma, and characterize injury patterns and VTE treatment methods.MethodsThe Pediatric Health Information System (PHIS) was queried from 2004 to 2013 using ICD-9 codes for lower extremity fractures (pelvis, femur, tibia, ankle, foot) and disl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…When comparing our results to other administrative database studies, the rate of VTE in children with SCD was found to be lower than the rate of VTE in pediatric cancer patients (5%), 26 comparable to VTE rate in children with congenital heart disease undergoing cardiac surgery (2.7%), 28 but higher than the VTE rate in children with trauma and lower-extremity fractures (0.05% to 0.2%). 29,30 The current work supports our recent, singleinstitution study, where the cumulative incidence of VTE in children with SCD followed at Nationwide Children's Hospital was estimated to be 2.9%, 16 and it adds to a growing body of literature.…”
Section: Discussionsupporting
confidence: 83%
“…When comparing our results to other administrative database studies, the rate of VTE in children with SCD was found to be lower than the rate of VTE in pediatric cancer patients (5%), 26 comparable to VTE rate in children with congenital heart disease undergoing cardiac surgery (2.7%), 28 but higher than the VTE rate in children with trauma and lower-extremity fractures (0.05% to 0.2%). 29,30 The current work supports our recent, singleinstitution study, where the cumulative incidence of VTE in children with SCD followed at Nationwide Children's Hospital was estimated to be 2.9%, 16 and it adds to a growing body of literature.…”
Section: Discussionsupporting
confidence: 83%
“…[6,23,25,29] Pediatric orthopedic postoperative VTE rates range from 0.05-0.1%, similar to our findings of 0.1%. [38][39][40] Orthopedic procedures were not the procedures with the highest VTE rate, but they were among the procedures with the highest overall VTE number (CPT code 22804, posterior arthrodesis of 13 or more vertebral segments, had 10 reported VTE events). However, NSQIP excludes trauma with the exception of isolated long bone fractures.…”
Section: Vte Rates By Surgical Subspecialty and Proceduresmentioning
confidence: 99%
“…Deep venous thrombosis (DVT) is a common disease with potentially serious consequences such as pulmonary embolism (PE). It should be noted that venous thromboembolism (VTE) includes both DVT and PE [ 1 , 2 ]. The incidence of DVT in the general population is between 1.6 and 1.8 per 1.000 per year [ 1 ].…”
Section: Introductionmentioning
confidence: 99%